Influence of rurality on the awareness of myocardial infarction symptoms in the US. (December 2019) - Tran, Phoebe; Tran, Lam
Background: Myocardial infarctions (MIs) are the leading cause of death in the United States (US). Differences in MI mortality rates exist between rural and urban areas in the US. Early recognition of MI symptoms can lead to receiving prompt lifesaving treatment. In this study, we identified the influence of living in a rural area, rurality, on disparities in MI symptom awareness across the US. Methods: We examined 2007 and 2009 Behavioral Risk Factor Surveillances System survey data using logistic regressions to model the impact of rurality on MI symptom awareness while controlling for sociodemographic and MI clinical factors. From the results of these models, we created a type of marginal probability, known as average adjusted predictions (AAPs) and the difference in AAPs, called average marginal effects (AMEs), to determine patterns of awareness for each MI symptom between rural, suburban, and urban areas. Results: We found that there were similar odds and probabilities of being aware of all five MI symptoms between rural, suburban, and urban areas, although rural residents consistently had a slightly higher odds and probability of being aware of all five MI symptoms compared with suburban and urban residents. Rural, suburban, and urban residents had the highest probability of being aware of chest pain/discomfort (95.5–96.1%) and the lowest probability of being aware of jaw/back/neck pain (68.6–72.0%). After adjustment, more than 25% of rural, suburban, and urban residents were found to be unaware that jaw/back/neck pain and feeling weak/light-headed/faint were symptoms of MI. AMEs were greatest for all areas for jaw/back/neck pain (−3.5% to −3.2%) and smallest for chest pain/discomfort (−0.6% to −0.2%). Conclusions: The study's results highlight the need to increase awareness of the MI symptoms of jaw/back/neck pain and feeling weak/light-headed/faint to shorten hospital delay and time to treatment, especially for rural areas where cardiovascular disease mortality is high.